2017
DOI: 10.19111/bulletinofmre.336625
|View full text |Cite
|
Sign up to set email alerts
|

The Geological Evolution of Sorgun (Yozgat)-Yildizeli̇ (Si̇vas) Foreland Basin, Petrographic, Geochemical Aspects and Geochronology of Volcanism Affecting the Basin

Abstract: Sorgun-Yıldızeli basin is an east-west trending asymmetric marginal foreland (peripheral foreland basin) formed as a result of the consumption of oceanic crust of the northern branch of Neotethys due to the collision of Sakarya continent in the north and Kırşehir Block in the south. It provides much information about the geodynamic evolution of the region. The basement of the study area consists of Late Palaeozoic-Mesozoic Akdağmadeni Massif. Akdağmadeni Massif was intruded by CenomanianMaastrichtian granitoid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 29 publications
0
6
0
1
Order By: Relevance
“…7). Akçay and Beyazpirinç (2017) and Göçmengil et al (2018) also indicated that fractional crystallization processes were effective in the development of Eocene volcanics, crop out in Almus, Yıldızeli, Kiremitli and Pazarcık area, at the west of the study area.…”
Section: Major Elements Geochemistrymentioning
confidence: 81%
See 3 more Smart Citations
“…7). Akçay and Beyazpirinç (2017) and Göçmengil et al (2018) also indicated that fractional crystallization processes were effective in the development of Eocene volcanics, crop out in Almus, Yıldızeli, Kiremitli and Pazarcık area, at the west of the study area.…”
Section: Major Elements Geochemistrymentioning
confidence: 81%
“…The plots of these values on the SiO 2 versus K 2 O/P 2 O 5 diagram show that the effects of crustal contaminations increase from basaltic trachyandesites towards trachyte (Figure 10b). Akçay and Beyazpirinç (2017), indicated that subduction zone enrichment and/or crustal contribution had important part in magmas generated Pazarcık and Kiremitli volcanics, and these more significant in Kiremitli volcanics. Göçmengil et al (2018) indicated that Almus volcanics had negligible amounts of crustal contamination comparing with Yıldızeli volcanics.…”
Section: Crustal Contaminationmentioning
confidence: 99%
See 2 more Smart Citations
“…The upper Cretaceous and Lutetian units in the study area are the products of submarine volcanism (Özcan et al, 1980). The Neogene units consisting of sand, clay and lacustrine sediments are the youngest deposits in the region (Ketin, 1966;Akçay and Beyazpirinç, 2017; Figure 1). The ophiolitic series and lower Eocene rocks underwent several deformation events and therefore, metamorphics and crystalline basement rocks, serpentines and radiolarite-bearing ophiolitic series and lower Eocene layers were intensely fractured and folded.…”
Section: Geological Settingmentioning
confidence: 99%